Magnolia quangninhensis (Magnoliaceae), a new species from northern Vietnam - Vu, Quang Nam; Xia, Nian-He; Nguyen, Thi Tho; Khuat, Thi Hai Ninh (Phytotaxa, 2020)
A new species of the family Magnoliaceae, Magnolia quangninhensis Q.N. Vu & N.H. Xia from Yen Tu National Forest, in the Quang Ninh Province, north of Vietnam is described and illustrated. It is most closely related to M. bawangensis and M. shangsiensis, but differs by having all parts of tree glabrous (except for dense brown sericeous tomentose to tomentulose brachyblasts), larger elliptic-obovate leaves, creamy-white to pink–purple tepals and stamens, and (6–)9–11 tepals.